ANALISIS KEBERLANJUTAN PROGRAM PENGENTASAN KEMISKINAN BERBASIS BANTUAN KOMODITAS AYAM DI NTB - Putra Adnyana, I Putu Cakra; Panjaitan, Tanda; Astiti, Luh Gde Sri; Hipi, Awaludin (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 14 No 1 (2020): Vol. 14 No. 1, 2020, 2020)
The medium-term program in agriculture-based poverty alleviation in NTB Province provides 50 chickens per poor household (RTM). There were 12,163 RTM participating in the BEKERJA program in the West and East Praya Districts. The purpose of the assessment is the recommendation option to support the alleviation of poor households based on chicken commodity assistance in NTB after the BEKERJA program. Activities in 2019 in 6 villages in West and East Praya Districts, Central Lombok District, NTB Province. Data collected through study, survey, FGD, tabulated then analyzed descriptively, stakeholder analysis. Generally the BEKERJA program increases RTM capacity in KUB chicken farming, improves RTM nutrition through the consumption of eggs and chicken meat, there are business opportunities for KUB chickens.